Organizational crises and reactions from a legitimacy perspective: Results from two multiple-case studies - Heiko Breitsohl (University of Wuppertal, Schumpeter School of Business and Economics, 2009)
Organizational crises can be conceptualized as interactions between organizations and stakeholders around the breach and reestablishment of common norms and social codes, i.e. perceptions of legitimacy. This paper contributes to the understanding of organizational crises by exploring the roles of dimensions of legitimacy in organizational crises as well as the role of different reactions in the resolution of crises. Results of two qualitative multiple-case studies based on analyses of media reports are presented. They suggest that crises are indeed characterized by a loss in legitimacy, the specific dimensions depending on the type of crisis. Moreover, results support the notion that the type as well as the timing of organizational reactions to crises is relevant to the effective handling of threatening events.
urn:nbn:de:hbz:468-20090785
Keywords: 650; Krisenmanagement; Organisation; Organisatorischer Wandel